Lactate Dehydrogenase and Hepatic Transaminases as Prognostic Markers of Hypoxic Ischaemic Encephalopathy in Neonates with Perinatal Asphyxia - VIJAYAKUMAR BALAKRISHNAN; SHAHIN MOHAMMED; KALPANA DEVADATHAN; LALITHA KAILAS (JCDR Research and Publications Pvt. Ltd., 2020)
Introduction: Hypoxic Ischaemic Encephalopathy (HIE) following perinatal asphyxia, due to cerebral hypoxia is an important cause of neonatal morbidly and mortality. Hypoxia causes cell death in various tissues like liver, kidney and muscles also. The leakage of enzymes from the dying cells causes elevation of Lactate Dehydrogenase (LDH), Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST) etc. Aim: To investigate whether serum LDH, ALT and AST levels in the first 12 hours of birth can be used as a predictor of severe HIE and/or the neurodevelopmental outcome at one year of age. Materials and Methods: A prospective longitudinal diagnostic test evaluation was done on in neonates with perinatal asphyxia admitted in a tertiary level neonatal intensive care unit in South India from March 2014 to September 2015 (18 months). Blood was collected for assay of LDH, AST and ALT within the first 12 hours of life. They were staged using the Levene's modification of Sarnat and Sarnat into stage1, 2 and 3 (mild, moderate and severe) on day 3. The survived babies were assessed for the neurodevelopment using the Development Assessment Scale for Indian Infants (DASII) at 4, 8 and 12 months. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy were calculated for each of these enzymes in predicting severe HIE and adverse neurodevelopmental outcome. Results: Out of the 76 babies with perinatal asphyxia, 27 had mild HIE, 17 had moderate HIE, 16 had severe HIE and 6 babies died and 10 were not having HIE. On follow-up of 36 infants for a period of one year, 69% had normal development, 8% each had mild and moderate delay and 14% had severe delay in development. For LDH, a cut-off value of 92.8 IU/l and 1153IU/l had good sensitivity and specificity for severe HIE and mortality respectively. A cut-off value of 38.5 and 36 were obtained in case of ALT and AST in case of severe HIE; the values were 47.5 and 41.5, respectively in case of mortality. The values had good sensitivity, but specificity was found to be low. A cut-off value of 919 IU/l of LDH showed good sensitivity and specificity in predicting severe developmental delay. Conclusion: Elevated LDH levels during first 12 hours of birth was found to be the best predictor of severe HIE, mortality as well as adverse neurodevelopmental outcome at one year of age in this study. AST and ALT levels also had significant predictive value in identifying severe HIE, but not in predicting outcome. These biochemical parameters are relatively inexpensive, easily available in most centers, can be used effectively to identify HIE early enough, as it is difficult to stage HIE if the baby is ventilated and on muscle relaxants and sedative antiseizure drugs, so that neuroprotective strategies like hypothermia can be started at the earliest.